2014
DOI: 10.1038/srep05255
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetoelectric coupling in magnetically short-range ordered Bi5Ti3FeO15 film

Abstract: Multiferroic materials, which offer the possibility of manipulating the magnetic state by an electric field or vice versa, are of great current interest. However, single-phase materials with such cross-coupling properties at room temperature exist rarely in nature; new design of nano-engineered thin films with a strong magneto-electric coupling is a fundamental challenge. Here we demonstrate a robust room-temperature magneto-electric coupling in a bismuth-layer-structured ferroelectric Bi5Ti3FeO15 with high fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 45 publications
5
71
2
1
Order By: Relevance
“…This leakage-related contribution was also confirmed in earlier reports [14,27,28] and seems to be intrinsic. As for undoped BTF [14] and Co-doped BTF [28] systems the positive-up-negativedown measurements confirmed that the ferroeletricity of BTF systems, although leaky, is intrinsic and natural and the leakage current does not play a big role in the ferroelectric behavior. Therefore, similarly, P-E loops shown in Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This leakage-related contribution was also confirmed in earlier reports [14,27,28] and seems to be intrinsic. As for undoped BTF [14] and Co-doped BTF [28] systems the positive-up-negativedown measurements confirmed that the ferroeletricity of BTF systems, although leaky, is intrinsic and natural and the leakage current does not play a big role in the ferroelectric behavior. Therefore, similarly, P-E loops shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…It has been known that the structural deviation of displacive ferroelectrics away from the underlying parent structure with a high symmetry is attributed to the origin of ferroelectricity. For the Aurivillius phase, the contributions of atomic displacement of A-site ions [29] or B-site ions [14,30] to the ferroelectricity have been reported controversially. However, on the basis of Rietveld refinement results, Ahn proposed that the displacement of B-site ions is the main structural cause of ferroeletricity in Mn-doped BTF system [19].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to solve these problems, several attempts have been made to synthesize rare-earth [5][6][7][8][9][10][11][12][13] or other elements [14] modified BFO or/and fabricate its solid solution and/or composites with other ferroelectric/ferrites [15]. In view of the above, structural, dielectric, electrical and magnetic properties of a new multioferroic fabricated with ferroelectric Bi 4 Ti 3 O 12 (T c = 650°C) and BiFeO 3 in equal molecular ratio (i.e., Bi 5 Ti 3 FeO 15 ) have been reported [16][17][18][19][20][21][22][23][24]. Because of multiple advantages of addition of lanthanum in ferroelectrics or/and multiferroics, we have recently carried out extensive studies of structural, dielectrics and ferroelectric properties of La modified ferroelectric/multiferroics Bi 5 Ti 3 FeO 15 , and reported some of them [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As candidates with the potential to become a single-phase multiferroic material exhibiting simultaneous coexistence of ferroelectric (FE) and ferromagnetic (FM) orders, layer-structured oxides with a general formula of Bi n+1 Fe n−3 Ti 3 O 3n+3 (n denotes an integer corresponding to the number of the sandwiched perovskite layers) have attracted increasing attention in recent years [4][5][6]. Recently, numerous studie s regarding to the realization of a remarkable coexistence of FE and FM properties at room temperature (RT) from these layered oxides by chemical modifications, e.g., various A-or B-site doping, have been reported [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%